2021
DOI: 10.1111/febs.16199
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a small molecule splicing inhibitor targeting UHM domains

Abstract: Splicing factor mutations are frequent in myeloid neoplasms, blood cancers, and solid tumors. Cancer cells harboring these mutations present a particular vulnerability to drugs that target splicing factors such as SF3b155 or CAPERα. Still, the arsenal of chemical probes that target the spliceosome is very limited. U2AF homology motifs (UHMs) are common protein interaction domains among splicing factors. They present a hydrophobic pocket ideally suited to anchor small molecules with the aim to inhibit protein-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Recently, a high throughput screening identified a small molecule, UHMCP1, which prevents the SF3B1/U2AF65 interaction. UHMCP1 interacts with the hydrophobic pocket of the U2AF65 UHM domain, thus strongly impacting RNA splicing and cell viability of cancer cells [ 80 ]. Another study identified phenothiazine derivatives, such as 7,8-dihydroxyperphenazine and 7,8-dimethoxyperphenazine, as molecules targeting the early assembly of the spliceosome [ 81 ].…”
Section: Splicing-based Therapeutic Strategiesmentioning
confidence: 99%
“…Recently, a high throughput screening identified a small molecule, UHMCP1, which prevents the SF3B1/U2AF65 interaction. UHMCP1 interacts with the hydrophobic pocket of the U2AF65 UHM domain, thus strongly impacting RNA splicing and cell viability of cancer cells [ 80 ]. Another study identified phenothiazine derivatives, such as 7,8-dihydroxyperphenazine and 7,8-dimethoxyperphenazine, as molecules targeting the early assembly of the spliceosome [ 81 ].…”
Section: Splicing-based Therapeutic Strategiesmentioning
confidence: 99%
“…UHMCP1 ( 1 ) and analogs ( 2 – 7 ) were prepared via a reaction sequence of reductive amination and subsequent deprotection of Boc group using HCl or hydrolysis of an ester group as shown in Scheme . Note that UHMCP1 ( 1 ) and 4 have four stereoisomers according to the report, whereas 2 , 3 , and 5 – 7 have two stereoisomers, respectively.…”
mentioning
confidence: 92%
“…The binding affinity of UHMCP1 to other three UHM domains was much weaker. Based on the microplate assay, UHMCP1 had an IC 50 value of 30 μM to U2AF2-UHM . When the amine group was positioned in the fused diazabicyclo-octane ring, the IC 50 values of 2 to SPF45-UHM, RBM39-UHM and PUF60-UHM were not markedly changed but were ∼5-fold lower with U2AF1-UHM.…”
mentioning
confidence: 97%
See 2 more Smart Citations